2018
DOI: 10.1515/jpm-2016-0282
|View full text |Cite
|
Sign up to set email alerts
|

Tokophobia (fear of childbirth): prevalence and risk factors

Abstract: Objective: To identify the prevalence of and to determine the risk factors for developing a fear of childbirth (tokophobia). Methods: We evaluated 191 pregnant women during Parenting and Childbirth Classes. Participants were approached when attending Parenting and Childbirth Classes between June 2014 and September 2014 and were asked to complete several questionnaires related to depression (CES-D), anxiety (STAI X1 and X2), satisfaction with life (SWLS), delivery expectation/experience (W-DEQ), and specific fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
55
2
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 25 publications
8
55
2
12
Order By: Relevance
“…Àâ-ñòðàë³éñüêå äîñë³äaeåííÿ ïîêàçàëî, ùî 48 % ae³íîê ïîâ³äîìèëè ïðî ïîì³ðíó òîêîôîá³þ ³ 26 % âèÿâèëè ñèëüíèé ñòðàõ ïåðåä ïîëîãàìè. Çà ðåçóëüòàòàìè äîñë³äaeåííÿ çðîçóì³ëî, ùî ñòðàõ ïåðåä ïîëîãàìè ñóòòºâî âïëèâຠíà ¿õ ðåçóëüòàò, ùî ïðèçâîäèòü äî çá³ëüøåííÿ ÷àñòîòè ïåðèíàòàëüíèõ óñêëàäíåíü òà êåñàðåâîãî ðîçòèíó [9].…”
Section: т м коValenkounclassified
“…Àâ-ñòðàë³éñüêå äîñë³äaeåííÿ ïîêàçàëî, ùî 48 % ae³íîê ïîâ³äîìèëè ïðî ïîì³ðíó òîêîôîá³þ ³ 26 % âèÿâèëè ñèëüíèé ñòðàõ ïåðåä ïîëîãàìè. Çà ðåçóëüòàòàìè äîñë³äaeåííÿ çðîçóì³ëî, ùî ñòðàõ ïåðåä ïîëîãàìè ñóòòºâî âïëèâຠíà ¿õ ðåçóëüòàò, ùî ïðèçâîäèòü äî çá³ëüøåííÿ ÷àñòîòè ïåðèíàòàëüíèõ óñêëàäíåíü òà êåñàðåâîãî ðîçòèíó [9].…”
Section: т м коValenkounclassified
“…Another factor that affects the expression of pain by women is fear. The ignorance of primiparous women regarding their ability to cope with childbirth leads, in most cases, to the first birth being the most painful, since later the women know about the process, and fear decreases with knowledge [ 5 , 11 , 12 ]. Women who had a bad experience in a previous birth often have similar pain and anxiety levels as primiparous women, since, although they know what they are facing, the previous negative experience increases their anxiety and fear, leading to the perception and expression of childbirth pain [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tokophobia is classified as an anxiety disorder that has been reported in many high-income countries and recent research from Europe has attempted to identify causes of FOC (Demsar et al, 2018;Sioma-Markowska, _ Zur, Skrzypulec-Plinta, Machura, & Czajkowska, 2017). Symptoms include tension, anxiety, depression, distressing thoughts, and stress (Rondung, Thomten, & Sundin, 2016).…”
mentioning
confidence: 99%
“…The most common explanations reported were fear of the pain of labor, anxieties about the health of the child, anxiety about the possibility of childbirth complications and about the loss of control. It seems that women with experience of sexual abuse and traumatic experience of former birth are more susceptible to FOC (Demsar et al, 2018). Research has shown that pregnant women with a pronounced FOC run significantly higher risks of birth complications with resulting psychological trauma than women without a pronounced FOC (Alehagen, Wijma, & Wijma, 2006).…”
mentioning
confidence: 99%